Design and performance projection of symmetric bipolar charge‐plasma transistor on SOI. Issue 20 (1st September 2014) - Sahu, C.; Ganguly, A.; Singh, J.
Abstract : A novel symmetric structure of bipolar charge‐plasma transistor (BCPT) is presented. It consists of symmetrical gates with platinum on top of a thin intrinsic silicon film, which forms hole plasma in emitter and collector regions. The base contact is formed with hafnium metal to induce electron plasma; hence, a p–n–p charge‐plasma transistor is formed without any doping. The collector area that is chosen is the same as an emitter to make the device symmetrical. 2D simulation results revealed that the proposed BCPT possesses higher collector current and higher current gain than conventional p–n–p bipolar junction transistor (BJT) and almost the same characteristics such as asymmetrical p–n–p BCPT for different geometries. The major challenge of poor cut‐off frequency ( fT ) of BCPT is also addressed by optimising the silicon film thickness and intrinsic gaps.